2014
DOI: 10.1111/jns.12086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic control on corneal nerves and peripheral neuropathy in streptozotocin‐induced diabetic C57Bl/6J mice

Abstract: We sought to determine the impact that duration of hyperglycemia and control has on corneal nerve fiber density in relation to standard diabetic neuropathy endpoints. Control and streptozotocin-diabetic C57Bl/6J mice were analyzed after 4, 8, 12 and 20 weeks. For the 20 week time point five groups of mice were compared: control, untreated diabetic, and diabetic treated with insulin designated as having either poor glycemic control, good glycemic control or poor glycemic control switched to good glycemic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 38 publications
(64 reference statements)
4
61
0
1
Order By: Relevance
“…Previous and our studies have confirmed that streptozotocin injection-induced type 1 diabetic mice assumed typical characteristics of diabetic corneal neuropathy, including impaired corneal nerve regeneration with concomitant attenuated corneal sensory and trophic functions102021. Given the capacity of VEGF-B to restore the anatomic and function corneal innervations in normal mice, here we explored the contribution and mechanism of VEGF-B in diabetic corneal nerve fiber regeneration, corneal sensation and trophic function recovery by using type 1 diabetic mice and cultured trigeminal ganglion neurons.…”
supporting
confidence: 77%
“…Previous and our studies have confirmed that streptozotocin injection-induced type 1 diabetic mice assumed typical characteristics of diabetic corneal neuropathy, including impaired corneal nerve regeneration with concomitant attenuated corneal sensory and trophic functions102021. Given the capacity of VEGF-B to restore the anatomic and function corneal innervations in normal mice, here we explored the contribution and mechanism of VEGF-B in diabetic corneal nerve fiber regeneration, corneal sensation and trophic function recovery by using type 1 diabetic mice and cultured trigeminal ganglion neurons.…”
supporting
confidence: 77%
“…The cornea is the most densely innervated structure of the human body, containing Aδ and unmyelinated C fibers derived from the ophthalmic division of the trigeminal nerve21. CCM is gaining establishment as a valid measure of diabetic nerve damage in the clinic2223 that can also be used to monitor diabetic neurodegeneration in rodent models171824. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sub-epithelial corneal nerves were imaged in vivo non-invasively using the Rostock cornea module of the Heidelberg Retina Tomograph (Heidelberg Engineering, Vista, CA) confocal microscope as previously described (Yorek et al, 2014; 2015). …”
Section: Methodsmentioning
confidence: 99%